Impact of Public Expenditures on the Dynamics of Economic Development of the Republic of Bulgaria - Mitkov, Milen (Dr. Viktor Koval, 2022)
Introduction. Regardless of the degree of government intervention in the economy, government spending is huge and often dominant in fiscal policy. Given the fact that costs are the main tool for fulfilling the economic and social functions of the state, adequate measures are needed to maximize their provision. The main goal of economic policy in Bulgaria is to ensure high economic growth in order to reach the average levels of Gross Domestic Product (GDP) per capita in the EU, therefore it is requires to identify all instruments that can affect the level of aggregate production. Aim and tasks. The purpose of this study is to analyze the main factors influencing the effectiveness of government spending on the basis of in-depth analysis and guidance on the implementation of public spending in the Republic of Bulgaria. The following main tasks have been set for the realization of the stated goal: disclosure of the essence and content, through theoretical statements about gross domestic product and government spending; carrying out an analysis of gross domestic product for the period 2010-2020; carrying out an analysis of government expenditures for the period 2010-2020; establishing a link between development of gross domestic product and government spending for the period 2010-2020. Results. Public spending has the potential to play the role of a kind of public lever for reducing the risks of poverty and social exclusion only when it is focused on the real causes of the problem and reaches the ultimate beneficiaries of the system. In 2020, compared to 2010, the gross domestic product increased by a little over BGN 46 million or by 63.8%.  The effect of the crisis was reflected in the main macroeconomic aggregates, with a negative rate of -0.4 compared to 2019. In 2020, compared to 2010, government spending increased by just over BGN 20 million or 76.4%.  Conclusions. During the considered period 2010-2020, there is a continuous economic growth both compared to the base year and compared to each subsequent year. For the entire period of the study, the pace of development of government expenditures outpaces the pace of GDP development. For the period 2010-2020 consolidated expenditures form a real share of redistribution through public finances in the ratio of about 35-40 percent of gross domestic product.